Sie sind auf Seite 1von 8

×

A × A C n

Ax = b

x b ×

A v C n

Av = λv

λ A v

Ax = b

v A λ

Av = λv

A

v 1 v 2

A =

3

0

0

1

λ 1 λ 2

v 1 =

1

1

A A =

3

1

v 2 =

1

1

1

3

 

λ C v

λ

= 0 0

Av = λv

Av λv = 0

(A λI) v = 0

I

I =

λv = λIv

1

0

0

0

.

0

1

0

.

.

.

.

.

.

.

.

.

.

.

0

0

1

A λI

A A λI

A =

a

a

1,1

2,1

a

a

1,2

2,2

A λI =

a 1,1 λ

a 2,1

a 1,2

a 2,2 λ

(A λI) v = 0 v

= 0 A λI

det (A λI) = 0

n

A

A =

A λI =

3

1

1

3

3 λ

1

1

3 λ

det (A λI) = (3 λ) 2 (1) 2 = λ 2 6λ + 8

λ = {2, 4}

A

A =

a

a

1,1

2,1

a

a

A λI =

a 1,1 λ

a 2,1

1,2

2,2

a 1,2

a 2,2 λ

det (A λI) = λ 2 (a 1,1 + a 2,2 ) λ a 2,1 a 1,2

+ a 1,1 a 2,2

det (A λI) = c n λ n + c n1 λ n1 + ··· + c 1 λ + c 0 = 0

λ i

A

Av = λ i v

v

v

1

n

=

λ 1 v 1

λ n v n

 n n n A {v 1 , v 2 , , v n } C n {v 1 , v 2 , , v n } x ∈ C n x = α 1 v 1 + α 2 v 2 + ··· + α n v n

{α 1 , α 2 , A

, α n } ∈ C x

Ax = A (α 1 v 1 + α 2 v 2 +

··· + α n v n )

Ax = α 1 Av 1 + α 2 Av 2 + ··· + α n Av n

Ax = α 1 λ 1 v 1 + α 2 λ 2 v 2 + ··· + α n λ n v n = b

x =

i

α i v i

 x

b =

i

α i λ i v i

Ax

x

A x

A =

3

1

1

3

x =

5

3

v 1 =

v 2 =

0

0

1

1

λ 1 = 3

λ 2 = 1

Av 1 =

3

1

Av 2 =

3

1

1

3

  

1

1

1

3

  

1

1

=

2

2

4

4

=

A

λ 1 = 2

λ 2 = 4

A v 1 v 2

Ax =

3

1

1

3

  

5

3

=

12

4

v 1 =

1

1

v 2 =

1

1

λ 1 = 2

λ 2 = 4

x

x = 4v 1 + v 2

x =

5

3

= 4

1

1

+

1

1

Ax = A (4v 1 + v 2 ) = λ i (4v 1 + v 2 )

Ax = 4 × 2   1

1

+ 4

1

1

=

12

4

A